Pengaruh Model Blended Learning Berbantuan Quipper School Terhadap Kemampuan Menulis Puisi Siswa Kelas X SMA Negeri 4 Binjai - Jusni Ekamastani Saragih; Elly Prihasti Wuriyani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to (1) Analyze the poetry writing ability of class X students at SMA Negeri 4 Binjai before using the blended learning model assisted by Quipper School; (2) Analyzing the poetry writing ability of class X SMA Negeri 4 Binjai students after using the blended learning model assisted by Quipper School; (3) Analyze the influence of the blended learning model assisted by Quipper School on the ability to write poetry in class X SMA Negeri 4 Binjai. The method used in this research is an experimental method with a one group pre-test post-test design research design. The population in this research is all students of class X SMA Negeri 4 Binjai, totaling 110 people and the sample in this research is students of class The data analysis technique used in this research is quantitative data by testing analysis requirements, homogeneity testing, homogeneity testing and hypothesis testing. The research results showed that the average score for students' poetry writing ability before using the blended learning model assisted by Quipper School was 57.77. The average score obtained by students after using the blended learning model assisted by Quipper School was 82.77% and was classified as good. Based on the results of the t test that was carried out, a value was obtained at a significant level of a = 0.05, the value of the t table provisions was 2.46 and the result of t = 13.06. So tcount ˃ ttable is 13.06 > 2.46, so ho (null hypothesis) is rejected and ha (alternative hypothesis) is accepted. Overall, it can be concluded that teaching using the blended learning model assisted by Quipper School has a positive effect on the results of the poetry writing ability of class X SMA Negeri 4 Binjai students.